Transformations in local social action in Portugal - Gonçalves, H.; Ferreira, J. (Societies, 2023)
The decentralization of social functions to municipalities, also known as municipal decentralization, triggered new contexts of practice in municipal social intervention. Municipalities are now dealing with more work and a focus on working in partnerships, which calls for greater dynamism of the local social action teams. This process has pushed the social workers to practices that alternate between mediation through the construction of access to a universal standard of social rights and the development of social intervention models with specific access to certain contexts and social groups. The objective of this paper is to envision new forms of standardization of social action within the framework of municipal decentralization, combining place-based perspectives with community and structural social work. What can we learn from social workers’ perspectives on the context of social functions in order to envision forms of place-based standardization of municipal social action? We seek to analyze the professional visions of local social action systems reform, discussing new contexts of practice; new place-based functions; and their correlation with political mediation for universal and intermunicipal social rights, instrumental dimensions of concrete work, and dimensions of value attributed to practicing social work. We organized the research according to the phenomenological paradigm, mobilizing the qualitative method and the multiple-case study. Based on evidence from the discourse of all professionals involved in the study, the findings indicate that the transformations of local social action systems, associated with the processes of social functions decentralization, imply greater comprehensiveness of social intervention, the ability to work in partnerships, and new place-based approach matrices, but they also present challenges for social workers in terms of multilevel governance that may favor the standardization of access to better social well-being between municipal territories.